2010
DOI: 10.1021/ie901626z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Thermodynamics of Zinc Phosphate Hydrate Synthesized by a Simple Route in Aqueous and Acetone Media

Abstract: Zinc phosphate (Zn3(PO4)2·4H2O) was prepared by a simple route using ZnO and H3PO4 in aqueous and acetone media at ambient temperature. Zn3(PO4)2·4H2O decomposes to Zn3(PO4)2 by three dehydration reactions, as revealed by thermal analytical (TG/DTG/DTA) and differential scanning calorimetry (DSC) techniques. The synthesized Zn3(PO4)2·4H2O and its dehydration product Zn3(PO4)2 were characterized by powder X-ray diffraction, Fourier transfer infrared, and scanning electron microscopy. Kinetic triplet parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…These growth media commonly contain inorganic phosphates, sodium, potassium, and chloride ions, as well as complex organic components including tryptone, yeast extract, soya peptone, and glucose. Zinc oxide has been demonstrated to form precipitates with phosphates, 29,30 complexes with chloride, 31 hydroxide ions, 32 and organic compounds such as citrate 33 and amino acids. 14 Despite the potential for any number of these components to react with the zinc oxide nanomaterials, this is rarely accounted for during tests of the antibacterial efficacy of zinc oxide.…”
Section: Introductionmentioning
confidence: 99%
“…These growth media commonly contain inorganic phosphates, sodium, potassium, and chloride ions, as well as complex organic components including tryptone, yeast extract, soya peptone, and glucose. Zinc oxide has been demonstrated to form precipitates with phosphates, 29,30 complexes with chloride, 31 hydroxide ions, 32 and organic compounds such as citrate 33 and amino acids. 14 Despite the potential for any number of these components to react with the zinc oxide nanomaterials, this is rarely accounted for during tests of the antibacterial efficacy of zinc oxide.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that effective anti-corrosion time was 408 h which was 158 h longer than zinc phosphate bulk materials on market. Because of the existence of crystal water inside the zinc phosphate crystal, a thin liquid layer formed in the surface of the product composed with Zn 2+ , PO 4 3and water. In the follow reaction equation, the M meant the composition of the metal basement.…”
Section: Anti-corrosion Effectmentioning
confidence: 99%
“…Meanwhile, the common technology of zinc phosphate production was hard to manufacture nanoscaled products. So, various techniques such as hydrothermal method [3][4][5], sol-gel method [6] and solid-state method [7] have been investigated for synthesis of zinc phosphate nanocrystals in the recent several years. However, these methods were difficult to be applied in the industry production because of the high cost and complicated technology.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc phosphate is non-toxic and an important multifunctional anticorrosive material for polymeric coatings, which has been studied extensively for potential applications such as plastic, electrical fields, medicine (dental cements) and anticorrosive coatings/pigment (Nevare et al, 2014;Boonchom et al, 2010). Nano-size fillers with low volume have been reported as efficient material over their conventional size materials.…”
Section: Introductionmentioning
confidence: 99%